Economy and Society (translated by Mariya Dobryakova) - Parsons, Talcott; Smelser, Neil (Journal of Economic Sociology, 2011)
The research perspective of «economy and society», renamed later into «old economic sociology», is associated with several icons of sociology, but ﬁ rst and foremost, — with Talcott Parsons and Neil Smelser. In their book with the same title «Economy and Society» the authors made an attempt to analyze the nature of disciplinary boundaries between economics and sociology from the standpoint of system theory. They claimed economic theory to be a special case of general theory of social systems and reinterpreted main economic categories as categories of the social system. We offer you ﬁ nal conclusions from this book.